2014
DOI: 10.3389/fnhum.2014.00725
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Somatosensory Reorganization in Children with Spastic Cerebral Palsy: A Multimodal Neuroimaging Study

Abstract: Although cerebral palsy (CP) is among the most common causes of physical disability in early childhood, we know little about the functional and structural changes of this disorder in the developing brain. Here, we investigated with three different neuroimaging modalities [magnetoencephalography (MEG), diffusion tensor imaging (DTI), and resting-state fMRI] whether spastic CP is associated with functional and anatomical abnormalities in the sensorimotor network. Ten children participated in the study: four with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 84 publications
7
93
0
Order By: Relevance
“…Laterality indices were shown to correlate with FA in the posterior limb of the internal capsule 174 as well as improve with constraint induced movement therapy (along with diffusion MRI measures) 170 . Resting state motor networks were shown to be altered in both unilateral and bilateral CP, with greater change in the non-dominant hemisphere in unilateral CP 171 . Perfusion MRI was also used to show that regions with diffusion MRI changes demonstrate reduced perfusion 189 .…”
Section: Diffusion Mri Used In Conjunction With Other Imaging Modalitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Laterality indices were shown to correlate with FA in the posterior limb of the internal capsule 174 as well as improve with constraint induced movement therapy (along with diffusion MRI measures) 170 . Resting state motor networks were shown to be altered in both unilateral and bilateral CP, with greater change in the non-dominant hemisphere in unilateral CP 171 . Perfusion MRI was also used to show that regions with diffusion MRI changes demonstrate reduced perfusion 189 .…”
Section: Diffusion Mri Used In Conjunction With Other Imaging Modalitiesmentioning
confidence: 99%
“…One study demonstrated increased MD in the dominant CST in unilateral CP 172 . In bilateral CP, one study also demonstrated bilateral reduced CST streamline count 176 , and another study demonstrated that FA and MD changes are more pronounced on the "more affected" side 171 . One study looked at children with dystonia, and showed no difference in FA of the CST from controls 177 .…”
Section: Corticospinal Tractmentioning
confidence: 99%
See 3 more Smart Citations